2011
DOI: 10.1002/smi.1328
|View full text |Cite
|
Sign up to set email alerts
|

Linking household income and work–family conflict: a moderated mediation study

Abstract: Research on the work-family interface has not often explored the role of structural characteristics such as income in the associations among work stressors, work-family conflict and family stressors. The goal of this study was to examine household income as a moderator of the relations among these variables. Results from a nationally (US) representative sample of 1472 employed individuals who were married with children indicate that the relations between work-to-family interference and family strain were stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…Most people experience some form of work-family conflict; however, that upper-income workers are more likely to have the resources to cope with the conflict when compared to their low-income counterparts. Odle-Dusseau, McFadden, and Britt (2015) noted that because of the increased resources and control over work, the negative impact of work-family conflict may be reduced for those individuals in high-earning jobs .Consistent with this, Ford (2011) found that while high levels of income did not appear to lower the rates of work-family conflict, higher levels of income did seem to provide resources to lower the influence of work-family conflict onto family strain.…”
Section: Financial Needsmentioning
confidence: 82%
“…Most people experience some form of work-family conflict; however, that upper-income workers are more likely to have the resources to cope with the conflict when compared to their low-income counterparts. Odle-Dusseau, McFadden, and Britt (2015) noted that because of the increased resources and control over work, the negative impact of work-family conflict may be reduced for those individuals in high-earning jobs .Consistent with this, Ford (2011) found that while high levels of income did not appear to lower the rates of work-family conflict, higher levels of income did seem to provide resources to lower the influence of work-family conflict onto family strain.…”
Section: Financial Needsmentioning
confidence: 82%
“…Consistent with these theories, studies link higher levels of economic deprivation (i.e. lower income) to a variety of OHP‐relevant individual outcomes, including work‐family conflict, depressive symptoms, and poorer health and well‐being, as well as organizational outcomes such as job attitudes, job performance and work‐family conflict (Brett, Cron, & Slocum, ; Chou et al, ; Deaton, ; Ford, ; George & Brief, ; Kim & Garman, 2003; Pereira & Coelho, ; Shaw & Gupta, ).…”
Section: Objective Financial Deprivationmentioning
confidence: 97%
“…Some researchers have suggested that the link between financial status, as a specific resource loss, and health is associated with the presence of chronic stressors. For example, individuals from disadvantaged socioeconomic classes and those who experience low‐income levels typically suffer from a greater number of chronic stressors, including financial insecurity, crowding, crime, noise pollution, discrimination, and WFC (Baum, Garofalo, & Yali, ; Ford, ). A recent review of 19 articles on the effects of the economic crisis that began in 2007 found that problems associated with the crisis, such as lowered wages or increased unemployment, were not only linked with increased mood disorders, but also to increased cardiovascular and respiratory diseases (Mucci, Giorgi, Roncaioli, Perez, & Arcangeli, ).…”
Section: Introductionmentioning
confidence: 99%
“…In an exception to the shortage of research on financial insecurity and work–family experiences, Ford () found that for low‐income compared to high‐income individuals, there were stronger relationships between WFC and family strain, as well as between family‐to‐work conflict (FWC) and family strain. Additionally, perceptions of a negative economic impact on one's life have been found to be related to greater WFC (Lauzun, Major, & Jones, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation